Risk of hereditary spherocytosis misdiagnosis due to limited effective diagnostic methods - Hien Thanh Dao; Triet Hy Van; Tuyet Thi Bach Tran; Dat Quoc Ngo; Anh Thi Mai Nguyen (Revista Cubana de Medicina Militar)
Introduction: Hereditary spherocytosis is a prevalent congenital hemolytic erythrocyte membranopathy. Laboratory diagnosis is traditionally based on erythrocyte morphology, yet 20% of cases may lack visible spherocytes, leading to misdiagnosis. The Eosin-5'-maleimide binding assay has emerged as a reliable diagnostic method.